2014
DOI: 10.1177/0272989x14551638
|View full text |Cite
|
Sign up to set email alerts
|

Where Is the Evidence? A Systematic Review of Shared Decision Making and Patient Outcomes

Abstract: Background Despite widespread advocacy for shared decision making (SDM), the empirical evidence regarding its effectiveness to improve patient outcomes has not been systematically reviewed. Purpose To systematically review the empirical evidence linking patient outcomes and SDM, when the decision-making process has been explicitly measured, and to identify under what measurement perspectives SDM is associated with which types of patient outcomes (affective-cognitive, behavioral, and health). Data Sources P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
733
1
10

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 940 publications
(764 citation statements)
references
References 72 publications
20
733
1
10
Order By: Relevance
“…20 SDM and the use of decision aids have been shown repeatedly to improve patients' satisfaction with their clinicians and health care. 21,22 Whether this potential for decreased liability is realized will depend largely on how well clinicians are able to implement SDM and build relationships with their patients in practice. …”
Section: Improved Patient-clinician Relationshipmentioning
confidence: 99%
See 1 more Smart Citation
“…20 SDM and the use of decision aids have been shown repeatedly to improve patients' satisfaction with their clinicians and health care. 21,22 Whether this potential for decreased liability is realized will depend largely on how well clinicians are able to implement SDM and build relationships with their patients in practice. …”
Section: Improved Patient-clinician Relationshipmentioning
confidence: 99%
“…Multiple studies have demonstrated that when patients use decision aids, there is a consistent tendency for them to choose to undergo fewer elective procedures. 21 While the impact of SDM on procedural decision making is not as well studied compared to the use of decision aids, patients' tendencies to choose fewer procedures when provided more information suggests that SDM may have a similar effect. Because invasive procedures are a frequent source of lawsuits, a reduction in the overall number may result in a reduction in the number of lawsuits as well.…”
Section: Reduction In Invasive Proceduresmentioning
confidence: 99%
“…A továbbiakban előtérbe került a terápiás együttműködés jelentősége, így a compliance, az adherencia javításának kommunikációs kérdéseiről indultak kutatások, majd jelentek meg review tanulmányok és metaanalízisek [3,28]. Ennek kapcsán került reflektorfénybe a közös döntéshozatal mechaniz musa [29], a motivációs interjú szemléletének és haté ÖSSZEFOGLALÓ KÖZLEMÉNY kony módszereinek használata a szomatikus orvoslásban [21]. Ma már az orvos-beteg kommunikáció résztéma köreinek is szinte beláthatatlan mennyiségű szakiro dalma van.…”
Section: "Az Orvosi Kommunikációval Kapcsolatos Ismeretek Inkább Szubunclassified
“…In their systematic review of SDM and patient outcomes, Shay and Lafata (2014a) concluded that when patients report on SDM (i.e. when they experience the decision-making process as shared) it results in significant improvements of affective-cognitive outcomes, such as knowledge, attitudinal, and affective-emotional effects.…”
Section: Introductionmentioning
confidence: 99%